Respuesta :
Answer:
-15x^5 + 26x^4 - 12x^3 + 35x^2 - 33x - 3
Step-by-step explanation:
(5x^3 - 2x^2 + 3x - 8) + (-3x^2 + 4x + 1)
do foil but with extra terms
-15x^5 + 20x^4 + 5x^3
+6x^4 - 8x^3 - 2x^2
-9x^3 + 12x^2 + 3x
+ 24x^2 - 32x - 8
combine like terms
(-15x^5 + 26x^4 - 12x^3 + 34x^2 - 29x - 8) - (4x - x^2 + 5) or -4x + x^2 - 5
-15x^5 + 26x^4 - 12x^3 + 35x^2 - 33x - 3
Answer:
[tex]x^3-4x^2+3x-12[/tex]
Step-by-step explanation:
[tex](5x^3-2x^2+3x-8)-(3x^2-4x-1)\\\implies 5x^3-2x^2+3x-8-3x^2+4x+1\\\implies 5x^3-5x^2+7x-7[/tex]
[tex](x^3-5x^2+7x-7)-(4x-x^2+5)\\\implies x^3-5x^2+7x-7-4x+x^2-5\\\implies x^3-4x^2+3x-12[/tex]